A review of the enigmatic monotypic genus Spathicranuloides Schedl, 1972, with a diagnosis for the subtribe Tesserocerina Strohmeyer (Coleoptera: Curculionidae: Platypodinae) - Levia, Nathaniel N.; Johnson, Andrew J.; Hulcr, Jiri (Zootaxa, 2026)
The monotypic genus Spathicranuloides Schedl represents an unusual pinhole ambrosia beetle (Coleoptera: Curculionidae: Platypodinae) genus endemic to Bougainville Island, Papua New Guinea. The genus and its only species Spathicranuloides moikui Schedl, 1972 were designated subjectively without an explicit description of its distinctive morphology. The genus and species are reviewed, illustrated, and redescribed. Spathicranuloides is compared with the other genera of Tesserocerini, particularly the genus Chaetastus Nunberg, with which it shares many morphological characters. A diagnosis for Tesserocerina is provided, and the placement of Spathicranuloides within Tesserocerina is confirmed and justified.